2017
DOI: 10.1177/1076029616689301
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prescribed Blood Products on the Incidence of Deep Vein Thrombosis and Pulmonary Embolism in Surgical Patients

Abstract: Deep vein thrombosis (DVT) and pulmonary embolisms (PEs) are common complications after surgical procedures. The influence of prescribed blood products on the occurrence of DVT and PE was evaluated in postsurgical patients in this retrospective case-control study. The records of 286 surgical patients were analyzed: DVT (n = 52), PE (n = 92), and a control group (n = 142). The amounts of prescribed blood, blood products, and vitamin K were reviewed, together with appropriate prescribing of low-molecular-weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Red blood cell transfusions have been associated with an increased risk of thrombosis in several settings, such as surgical patients, 59 surgical patients who could not be anticoagulated for medical reasons, 60 spine surgery, 61 subarachnoid hemorrhage, 62 and postpartum bleeding. 63 In trauma patients with massive transfusion, higher RBC usage was independently associated with higher VTE risk.…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cell transfusions have been associated with an increased risk of thrombosis in several settings, such as surgical patients, 59 surgical patients who could not be anticoagulated for medical reasons, 60 spine surgery, 61 subarachnoid hemorrhage, 62 and postpartum bleeding. 63 In trauma patients with massive transfusion, higher RBC usage was independently associated with higher VTE risk.…”
Section: Discussionmentioning
confidence: 99%
“…Most observational studies investigating VTE ignored the role of allogeneic blood transfusion as a causal factor. Few studies found in cancer and after surgery that blood transfusions were dosedependently associated with VTE [74][75][76]. One study in 1070 patients undergoing cardiac surgery found a dose-dependent association with transfusion of blood products and VTE [77].…”
Section: Allogeneic Transfusion and Thrombosismentioning
confidence: 99%